Clinical research : from proposal to implementation - McPhaul, Michael J.; Toto, Robert D.; Lee, Simon J. Craddock.; Sadler, John Z. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"Clinical and translational research is a crucial link to the improvement of clinical care and practice. Many of the elements that are involved--physicians, nurses, pharmacists, laboratory testing, medical records--are also involved in the delivery of care to patients. Yet in the conduct of clinical research, these elements are arrayed in different configurations and constrained by rules and regulations that are distinct from those that guide the practice of medicine. In parallel with these considerations, the conduct of clinical research demands a specific skill set. Specialized tools are required to formulate and design informative clinical trials and to interpret the findings from such experiments"--Provided by publisher.